The prospects of Palaeolithic research in Croatia - Karavanić, Ivor (2002)
The famous site of Krapina, the first Paleolithic site discovered in Croatia, was excavated about a century ago. Although during the last hundred years Paleolithic research has not been very intensive, several sites have yielded important evidence for the evolution of the Upper Pleistocene hominids and their material cultures. Paleolithic research was more intensive in north-western Croatia and Istria than in other parts of the country. Many analyses and reviews of old collections have been done in the last decade. In 1995, modern excavations were launched in Istria and Dalmatia and are still in progress, with up-to-date archaeological methodology for Paleolithic sites. Research there aims to provide new data on environmental conditions and hunter-gatherer adaptations in the Paleolithic and Mesolithic of the Eastern Adriatic region. Paleolithic research is often organised as collaborations between Croatian and foreign institutions.
Projekt MZOS
ENG